The nature of the religious right : the struggle between conservative evangelicals and the environmental movement - Pogue, Neall W., 1979- (Cornell University Press, 2022)
"The Nature of the Religious Right explores the history behind present day anti-environmental views held by white conservative evangelicals connected with the religious right movement"--